Design of Aromatic Interaction Networks in a Protein Cage Modulated by Fluorescent Ligand Binding - Yuki Hishikawa; Taiga Suzuki; Basudev Maity; Hiroki Noya; Michito Yoshizawa; Asuka Asanuma; Yuri Katagiri; Satoshi Abe; Satoru Nagatoishi; Kouhei Tsumoto; Takafumi Ueno (Advanced Science)
Abstract Dynamic behavior of proteins, such as orientation changes of aromatic residues, plays an important role in controlling biomolecular functions. Protein design that can precisely control such dynamic behavior at the atomic level is a challenging issue. The study reports the development of a system capable of orientational changes of aromatic side chains upon ligand binding. Aromatic pockets are constructed on the inner surfaces of protein cages to bind polycyclic aromatic fluorescent molecules to the targeted position by π–π stacking interactions. X‐ray crystal structural analysis indicated the cooperative orientation changes of the aromatic clusters around the pocket triggered by the ligand binding. A comparison of various ligands shows that the movement of aromatic clusters can be controlled depending on the ligand structures. Fluorescence quantum yield and fluorescence lifetime are enhanced due to isolation of the fluorescent molecules in an aromatic pocket. These findings provide an understanding of the unique molecular behavior and fluorescence properties of ligands due to the assembly of aromatic residues and a guideline for developing dynamically controlled supramolecular biomaterials.